Big Data's Future Potential as an Innovation in Competitive Advantage and Decision-Making Techniques - Kusumah, Armando; Sumarni, Teti; Harto*, Budi; Salim, Agus (JURISMA : Jurnal Riset Bisnis & Manajemen, 2024)
This research highlights the challenges of big data integration in organisational decision-making processes, illustrating the gap between big data capabilities and their effective utilisation. An analytical descriptive qualitative method was used to study the use of big data in supporting sustainable innovation and competitive advantage of organisations in Indonesia. The results show that big data can improve the effectiveness of decision-making strategies by understanding market trends and consumer behaviour, which contributes to improving organisational performance and competitive advantage. These results are expected to contribute to the strategic management and innovation literature and encourage business practices in designing effective big data strategies to achieve sustainable competitive advantage. Keywords: Big Data; Technological Innovation; Strategic Decision Making; Competitive Advantage; Sustainable Innovation